O trabalho docente e a discursividade da autopercepção dos professores de sociologia e filosofia no ensino médio em Toledo/Pr : entre angústias e expectativas - Eras, Lígia Wilhelms (2006)
In this presentation the look will be focus about teacher who act in average education, in the area of Sciences Human beings, in you discipline as Sociology and the Philosophy with regard to distinction position of these professors in this localization of education and condition of work. The study object, from the speech of the a professionals perception by themselves of these professionals, is to try to map the feelings of quandary and anguish provoked by the loss of paper and social function, in the presence of areas to know in the field technician in opposition to the action intellectual. The discipline them of Sociology and Philosophy especially is come back toward the reflection, and in contraposition, the school and the modern knowledge are established on the right of advance of the knowledge restored on the sign of the applicability technique. This perspective of boarding also unites the challenge to approach the dimension of the Language and the Society in the problematization around the teaching work. This research searched two lines arguable of construction. The first one will go to work concepts and theories that can enrich and also to contextualize the quarrel around the knowledge idea, modernity, social division of the work, intellectuality and technique. Second it is the treatment theoretician-metodologic of the research, based on the impact of the organization of the structure and the new sociability on the knowledge and the studing the action of the teaching work. In this field of formation of the ideas and mentalities the referencial theoretician-metodologic is Antonio Gramsci and Pierre Bourdieu, for, after that, elaborating a transposition of this structural organization for the composition of new styles of life, production, knowig and of the constitutuion of field professional, symbolic and institution as way of update of these citizens. For the structure, visualizing the place of its action. The model theoretician-metodologic chosen in Gramsci and Bourdieu will allow to think the reality of the school and the formation of average education, as well as the feeling of anguish of the social group of the professors of Sociology and Philosophy in average education, having as locus of research the city of Toledo/PR in its recent secular context.